Nusantara and Mitreka Satata: A Study of the Majapahit Foreign Policy in the 13th Century - Fernandes, Michael Aprillino; Luthfi, Ismail (Journal of Maritime Studies and National Integration, 2023)
In stanzas thirteen to fifteen of the Kakawin Negarakertagama, the regional terms "Nusantara" and "Mitreka Satata" are mentioned. Written by Pu Prapanca, the manuscript clearly elucidates the meanings and distinctions between these terms. Notably, the term "Nusantara" was already known during the Singhasari era, as evidenced by its appearance in the Camundi inscription under the name "Dwipantara." However, there remains considerable ambiguity and frequent misinterpretations regarding these terms, with some even conflating them. This research aims to clarify the meanings of "Nusantara" and "Mitreka Satata" and to delineate their differences. Additionally, the study explores the historical contexts and nuances associated with each term. This study employs historical methods with a philological approach, examining inscriptions, statues, and manuscripts categorized as artifacts. The results of this study shed light on the foreign policy of Majapahit as a state. The concept of territorial division was adopted by kingdoms on the island of Java and has been developing since ancient Javanese times. This concept was adhered to even during the Islamic Mataram era and the period of colonialism.